The Political Game in Alice Books: Carroll’s Satirical Vision of the Age (Journal of the College of Basic Education, 2022)
In 1865, Charles Lutwidge Dodgson, British Nonsense writer and mathematician, presented Alice in the Wonderland using Lewis Carroll as a penname. The story was classified as children fiction leaving all its embedded political symbols and bitter satire of the royals, army, parties and parliaments up to guessing and concluding till the real identity of the writer was revealed and the second part of the story Through the Looking Glass and What Alice Found There released in 1871. In these stories, Carroll satirically portrayed Britain as a wonderland for its political and social nonsenses describing the ruling system as a game. The queen, the king, the army, and the governors were depicted as playing cards and pawns of chess; each has his own role in this game and part of a larger scheme rules and laws. Politicians and parliaments, out of the new Darwinian vision, were no more than prestigious and high eloquent animals. Alice was a symbol of oppressed British citizen looking for an end for the political tunnel she fell in; all the resolutions and constitutional reforms did not fit her dreams or ambitions. This series became a political allegory that could be applied to the political discourse and critique in Media, journalism, literature and electoral campaigns every time and then; ‘fighting over the large piece of cake